Analysis of Consumption Behavior Using Social Commerce - Midrawati Hasibuan (Jurnal Mirai Management, 2022)
Introduction/Main Objectives: The focus of this research was to explore how students in management courses consume using the social media platform Instagram. Background Problems: The goal of this study was to find out how students in management classes use the social media site Instagram to buy things. Novelty: Analysis of consumption behavior using Instagram in Department of Management Universitas Al Washliyah. Research Methods: This study employs a qualitative phenomenological approach. Finding/Results: Management students have a logical approach to consumption. This is due to the fact that their consuming behavior includes the purchase of products and services. Before moving on to additional demands, students might prioritize their key needs. They consume products that are essential necessities such as primary, secondary, and tertiary demands. According to the findings of this study, management students use Instagram daily and for social purposes. Instagram Stories, Explore, and Likes are the most often used features. Students use Instagram Stories to follow the activities of their classmates and to share their everyday activities. Conclusion: Based on the results and discussion in the preceding section, it is possible to conclude that students majoring in economic development likely to consume products and services. Their social environment, namely their peers, influences their consumption habits. Students are also impacted by their age, life cycle development, lifestyle, personality, and self-concept. Student consumption control is beneficial